Efficacy of withdrawal or tapering of bDMARDs vs. standard regimen in axial spondyloarthritis patients: systematic review and meta-analysis informing the update of the Spanish Society of Rheumatology Guideline - Park, Hye Sang; Díaz del Campo, Petra; Plana, Maria Nieves; Polo y La Borda, Jessica; Guerra-Rodríguez, Mercedes; Moreno, Mireia; Cañete, Juan D. (Frontiers in Medicine, 2025)
ObjectivesTo assess efficacy of withdrawal or tapering biologic disease-modifying antirheumatic drugs (bDMARDs) vs. maintaining a standard regimen in patients with axial spondyloarthritis (axSpA) to sustain remission.MethodsWe conducted a systematic review of randomized controlled trials (RCTs) through July 2025, comparing treatment discontinuation or tapering against standard bDMARDs regimens in axSpA. We included RCTs of axSpA patients randomized to treatment interruption or tapering compared with standard treatment regimens. Outcomes measures included remission or flare measured by Ankylosing Spondylitis Disease Activity Score (ASDAS), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and acute phase reactants. We rated the certainty of evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) system. We presented dichotomous outcomes as risk ratios (RR) with their 95% confidence intervals (CI). We used a random-effect model to perform a pooled analysis.ResultsEight RCTs involving 1,384 participants were analyzed. For those in sustained remission >6 months, withdrawal led to a significantly lower rate of inactive disease state (RR 0.58, CI 0.45–0.76; high certainty) and increased risks of flare (RR 1.79, CI 1.34–2.38; high certainty) and partial flares (RR 1.57, CI 1.25–1.97; high certainty) compared to the standard regimen. Patients with short-term remission <6 months and treatment withdrawal experienced significantly higher rates of flares (RR 0.41 CI 0.23–0.72, low certainty) and increased disease activity (RR 0.36 CI 0.15–0.86, low certainty). Tapering in 211 patients showed non-significant risk reductions in maintaining remission or low disease activity (RR 0.89, CI 0.66–1.18; moderate certainty).ConclusionTreatment withdrawal reduces the likelihood of maintaining inactive or low disease activity. Tapering does not significantly compromise the maintenance of remission or low disease activity offering a safer alternative to complete treatment withdrawal.